(untitled) (American Journal of Business Management, Economics and Banking, 2025)
Issues such as strategic investors, adaptation to market principles, elimination of dependence on state funds and creation of equal competitive conditions are defined as the main directions of the banking system reform strategy. The transition of banks to this process requires changing their business models. This article is an important scientific and practical aspect in the process of expanding the income base of commercial banks in the process of transformation.